Incisional hernia and enterocutaneous fistula in patients with chronic intestinal failure: prevalence and risk factors in a cohort of patients referred to a tertiary centre. (15th July 2019) - Hodgkinson, J. D.; Oke, S. M.; Warusavitarne, J.; Hanna, G. B.; Gabe, S. M.; Vaizey, C. J.
Abstract: Aim: This study aims to determine the prevalence of incisional hernia (IH) and enterocutaneous fistula (ECF) in patients with intestinal failure (IF) referred to a tertiary centre and to identify factors associated with their development. Method: A retrospective case note review was undertaken of a prospectively maintained database of all patients on home parenteral nutrition between 2011 and 2016 at a UK tertiary referral centre for IF. Risk factors were identified using binary logistic regression. Results: The database search identified 447 patients, of whom 349 (78.1%) had surgery prior to developing IF. Eighty‐one (23.2%) patients had an IH and 123 (35.2%) had an ECF at the time of referral. Of these, 51 (14.6%) had both IH and ECF. IH was associated with a high body mass index ( P  = 0.05), a history of a major surgical complication resulting in IF ( P  = 0.01), previous emergency surgery ( P  = 0.04), increasing number of operations ( P  = 0.02) and surgical site infection (SSI; P  = 0.01). ECF was associated with complications relating to earlier surgery. ( P  ≤ .001), previous treatment with an open abdomen ( P  = 0.03), SSI ( P  = 0.001), intra‐abdominal collection ( P  ≤ 0.001) and anastomotic leak ( P  = 0.02). Conclusion: In this series, patients with IF had a prevalence of IH which was more than double that expected following elective laparotomy (about 10%) and one in three had an ECF. Risk factors for IH and ECF are discussed.